The public school also has the right to a professional management - Álvarez Fernández, Manuel (Avances en Supervisión Educativa, 2006)
Definir el perfil profesional para la dirección de la escuela pública es una oportunidad que suscita resistencias y temores. Esta dirección estaría fundamentada en la absoluta confianza de la Administración en la capacidad del director, en la evaluación externa o accountability, en la incentivación personal de carácter institucional o económico y en la capacidad del director para intervenir en la asignación del personal del centro. En los sistemas educativos de los países europeos de nuestro entorno se identifican algunos criterios que suelen estar presentes en la dirección escolar: el modo de acceso, formación específica, experiencia docente y en la coordinación de grupos humanos y autonomía, entendida ésta como la capacidad de innovar y tomar decisiones. Abstract The chance of giving a definition of the professional profile of a Head Teacher in a publicly funded state school can easily cause to some extent both resistance and fears. This type of school management should be based on full confidence of educational authorities in the Head Teacher’s abilities, on external accountability, on providing a professional or economical incentive for the Head Teacher’s performance and, finally, on the Headmaster’s acquisition of the right to play a part in the assignation of personnel to the school. Some interesting criteria in school management are self-evident in the educational systems of other European countries: admission process, specific qualification, teaching experience, staff management experience, and independence, this last condition regarded as a capacity to innovate and to take decisions.